Zakat Disbursement Efficiency for Accountability and Prevention of Zakat Misappropriation - Setiawan, Nanang; Soewarno, Noorlailie (International Conference on Islamic Economic (ICIE), 2024)
This study aims to measure and analyze the efficiency of zakat distribution in Indonesia to achieve accountability and prevent zakat misappropriation. This study uses a desk study to collect data on zakat collection and distribution through the National Zakat Amil Agency (BAZNAS) and twenty-four Zakat Charity Institutions (LAZ) in Indonesia, with two indicators of ratio analysis: disbursement efficiency and cost efficiency. Disbursement efficiency is to see the zakat distribution efficiency level, and cost efficiency is to see the efficiency level of zakat management operational costs. The results show that almost all LAZs have been effective in distributing zakat, except Rumah Yatim Ar Rohman Indonesia (RYARI), with a ratio of 67% (fairly effective). The results of the operational cost efficiency ratio show that only four LAZs fall into the "within the limits of sharia provisions" category: RYARI, LAZIS Nahdlatul Ulama (LAZISNU), Nurul Hayat (NH), and Pesantren Islam Al Azhar (PIAA). This research is important to get a comprehensive picture of the efficiency of distributing zakat funds to BAZNAS and LAZ in Indonesia. This study contributes to policymakers, zakat management practitioners, and academics by increasing literacy in zakat management in an accountable manner and in the context of preventing zakat misappropriation